The Effect of Resistance Band Exercises Through Audio Visual on Learning Freestyle swimming at Club Garuda Laut Palopo - Amalia, Reski; Nur, Suaib; Zainuri, Muhammad Irham (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
Swimming is a sport that has great benefits. The problem for athletes, especially freestyle swimming, lies in technique, especially in the position of the hands and feet, sometimes athletes are not in line with what the coach expects. The purpose of the study was the effect of resistance band training through audio visual on freestyle swimming learning at Club Garuda Laut Palopo. This type of research is quantitative research that uses a one-group pretest-posttest design. This research is a pre-experimental research design. The population in this study was novice swimming athletes Club Garuda Laut Palopo. The population sampling technique in this study used saturated samples (census), which is a sampling technique where all populations were sampled as many as 5 novice swimming athletes. The research data was analyzed descriptively, the requirements test was the data normality and homogeneity test, and the T test used SPSS version 20.00. The results showed that the value of t = count of 2.958 was greater than t = table 2.571 or t = count of 2.958 > t = table 2.571 and sig results. (2-tailed) which is 0.000 < 0.05. This means that there is a significant influence of resistance band training through audio visual on freestyle swimming learning at Club Garuda Laut Palopo.